Remote assessment of learning during the pandemic: junior high school teachers’ experiences - Rizaldy Escobar Garcia; Monica Elaijan R. Macaballug; Edilberto I. Perez (Institute of Advanced Engineering and Science, 2024)
This paper explores the teachers’ experiences of remote assessment in the Junior High School of Rizal Technological University. The qualitative study was used to determine the assessment methods used during the remote learning in terms of written and performance task and identify the most effective among other difficulties faced by the teachers in comparison with face-to-face. Data of the paper were obtained by conducting interviews that use open-ended questions from 10 participants who teach in the School Year 2021-2022. The analysis of the study was done according to themes and categories and participants’ answers were quotes excerpted from the transcripts. The study’s conclusion emphasizes the significance of carefully planning exams to guarantee academic integrity. With emphasis on the need to focus on cognitive, emotional, and psychomotor abilities when designing learning exams, especially for online learning, as well as the use of technology tools to monitor results and prevent dishonest behavior during online assessments. Finally, a complementary technique for evaluating students while they are engaged in online learning through teaching resources or learning management systems must be available.